1970
DOI: 10.1172/jci106291
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of inhaled isoproterenol on the mechanical characteristics of the lungs in normal man

Abstract: A B S T R A C r We investigated the effects of isoproterenol on the pulmonary mechanics of eight healthy male subjects. We measured the flow-volume, pressurevolume, resistance-volume, and pressure-flow relationships of the lungs of our subjects in addition to the forced expiratory volume (FEV1). The results of this study confirm earlier observations that isoproterenol produces a considerable decrease in airway resistance but only small changes in maximum expiratory flow. Measurements of static pressure-volume … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
1
1

Year Published

1977
1977
1993
1993

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(18 citation statements)
references
References 24 publications
1
15
1
1
Order By: Relevance
“…It is of interest to compare in some detail our findings with those of McFadden et al (3). They were the first to point out that changes in Palv' could be used to interpret the distribution of airway resistance changes and, indeed, that such changes, according to EPP concepts, would be related to this distribution and to Pst(l), but unrelated to total airway resistance.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…It is of interest to compare in some detail our findings with those of McFadden et al (3). They were the first to point out that changes in Palv' could be used to interpret the distribution of airway resistance changes and, indeed, that such changes, according to EPP concepts, would be related to this distribution and to Pst(l), but unrelated to total airway resistance.…”
Section: Discussionmentioning
confidence: 52%
“…There was a small yet consistent decrease in air and HeO2 Rus after all three bronchodilator regimens. (3) demonstrated that isoproterenol given in large doses reduced Pst(l). These authors suiggested that this was the basis for the greater increases in airways conductance rather than in maximal flows.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, histochemical fluorescent techniques have shown an extensive network of catecholamine-containing nerves throughout the tracheobronchial tree [8], but it is not understood how these nerves exert their influence on the bronchial smooth muscle [9]. The sympathetic nervous supply to the adrenal gland is derived from the TI,-L, level.…”
Section: Discussionmentioning
confidence: 99%
“…It seems possible, however, that the interference of other factors associated with the bronchodilator treatment may counteract the effects predicted on the basis of the model originally proposed by Otis et al [18]. Because of the existence of bronchomotor tone in normal airways, which can be influenced by atropine or other bron chodilators [10,16,23,24], selective bronchodilation of high-resistance lung units seems unlikely. Participation of low-resist ance units in the response should tend to minimize the effects of bronchodilators on regional time-constant inequality; however, this mechanism can even be expected to ac centuate the inequality if the regional in crease in resistance results from organic changes in the airways rather than from bronchospasm, so that the response of the low-resistance units to the bronchodilator may be relatively more marked than that of high-resistance units.…”
Section: Discussionmentioning
confidence: 95%